Challenges, Inquiry, and Recommendations: Effective COVID-19 Vaccine Management in the Face of Public Mistrust and Concern - Caron, Rosemary M.; Dorsey, M. Girard (Frontiers in Communication, 2022)
By examining concerns about safety, compliance, and distribution through an interdisciplinary approach of public health and history, we argue that historical and contemporary mistrust of immunizations serves to challenge the successful management of a COVID-19 vaccine program in the U.S. Unique circumstances surrounding the development of a COVID-19 vaccine, including pressure for rapid production, unclear communication from public health officials, and existing resistance to behavioral protective public health policy measures (e.g., mask-wearing) complicate widespread vaccine adoption. Currently, the demand for first and second COVID-19 vaccine doses, as well as the COVID-19 booster, continues to fluctuate in the U.S. population as COVID-19 variants continue to emerge. This hesitancy has resulted in a stalled vaccination program and the absence of herd immunity. To support the successful management of a vaccine program, we recommend public health education and communication measures that can be tailored to local community needs while preparing realistic public expectations surrounding the efficacy of a COVID-19 vaccine. A tailored approach may reduce vaccine hesitancy in American society. The perspectives offered herein present a pathway that is applicable to the current COVID-19 vaccine management program in the U.S., other global locations, and future pandemics.